Islam through objects - Bigelow, Anna (Bloomsbury studies in material religion, 2021)
Introduction: Thinking with Islamic Things / Anna Bigelow -- Part I. Tracing Images: 1. Clothes of Righteousness: The MGT Uniform in the Twentieth Century / Kayla Renée Wheeler -- 2. The Masonic Muhammad: Modern Franco-Iranian Visual Encounters in Prophetic Iconography / Christiane Gruber -- 3. Repetition and Relics: Tracing the Lives of Muhammad's Sandal / Richard McGregor -- Part II. Identifying Objects: 4. "The Greatest and Only Flag Known": The Lapel Pin in American Islam / Michael Muhammad Knight -- 5. Tasbih in West African Islamic history: spirituality, aesthetic, politics, and identity / Ousman Murzik Kobo -- 6. Caps, Heads, and Hearts / Scott Kugle -- Part III. Objects in Practice: 7. What Comes to Light When a Lamp is Lit in Bektashi Tradition / Mark Soileau -- 8. The Agency of the Material Taviz (Amulet) in a South Indian Healing Room / Joyce Burkhalter Flueckiger -- 9. The Life of a Tablet / Aomar Bou -- Part IV. Circulatory Systems: 10. Coins and Fish: Sovereignty, Economy, and Religion in the Islamicate Indian Ocean / Roxani Eleni Margariti -- 11. The Aljibe del Rey in Granada / D. Fairchild Ruggles -- 12. Zamzam Water: Environmentality and Decolonizing Material Islam / Anna M. Gade -- List of Contributors -- Notes -- Bibliography -- Index.